Improving Efforts Learning Achievement In Science Subjects Through Demonstration Method Concerning The Properties Of Solid, Liquid And Gas Objects In Class IV - Kristianto, Adi (Universitas Sebelas Maret, 2022)
The aim of this research is to find out whether using the demonstration method can improve student achievement in learning science lessons in class IV of SD Negeri 2 Jetiswetan Semester II of the 2015/2016 academic year. The research location was in class IV of SD Negeri 2 Jetiswetan, Pedan District, Klaten Regency, Central Java, Indonesia. This research was carried out for 2 months from April to May 2016, in effective teaching activities. The subjects of this classroom action research were students of class IV of SD Negeri 2 Jetiswetan Klaten, in the second semester of the 2015/2016 academic year. Data collection techniques are through observation and through tests to obtain data about activities, researchers use observation format sheets and learning outcomes scores. So the author concludes that learning science using the demonstration method can improve science learning achievement for class IV students at SD Negeri 2 Jetiswetan in Semester II of the 2015/2016 school year.